2007
DOI: 10.1007/s11852-007-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of maritime public domain in the Portuguese Coastal management

Abstract: The coastal areas, unique spaces of extraordinary natural wealth, are attractive areas for economic and urban activities. These human interventions may easily interfere with their uniqueness and sensitivity, causing conflicts involving several uses and interests. In Portugal, such problems also occur in a specific zone of the coastal areas -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…In contrast, other authors refer to the need to update MPD related laws in order to improve coastal zone management like in Lebanon, criticized for dating from 1925 (Meliadou et al 2012), or in Italy, when compelled to integrate developments of international law (Rochette 2009). It is also the object of criticism on how it is implemented given some existing abusive uses over margins and of calls for its redesign using better knowledge, GIS tools, and stronger management measures (Pinho 2007). Similar approaches can be seen in relation to the Cuban maritime terrestrial public domain by Monzón Bruguera and Herrera Monzón Bruguera and Herrera Machado (2019).…”
Section: The Maritime Public Domain and The Protection Of Estuarine M...mentioning
confidence: 99%
“…In contrast, other authors refer to the need to update MPD related laws in order to improve coastal zone management like in Lebanon, criticized for dating from 1925 (Meliadou et al 2012), or in Italy, when compelled to integrate developments of international law (Rochette 2009). It is also the object of criticism on how it is implemented given some existing abusive uses over margins and of calls for its redesign using better knowledge, GIS tools, and stronger management measures (Pinho 2007). Similar approaches can be seen in relation to the Cuban maritime terrestrial public domain by Monzón Bruguera and Herrera Monzón Bruguera and Herrera Machado (2019).…”
Section: The Maritime Public Domain and The Protection Of Estuarine M...mentioning
confidence: 99%
“…In a recent study, Pinho (2007) identified no less than 4000 dwellings (not accounting businesses, industries or infrastructure) located in high risk areas over a 50 km stretch of this beach. The state response to this threat of an iconic coast was the successive building of heavy coastal defence infrastructures.…”
Section: Phase 1: Recognition Of Coastal Riskmentioning
confidence: 99%
“…Mas, hoje, ignorar os impactos sociais e econômicos da erosão costeira não é opção. Um estudo recente identificou 4000 construções em zonas de elevado risco num troço de 50 km entre as praias de Esmoriz e Vagueira, mais a norte (PINHO, 2007).…”
Section: Zonas Costeiras Em Mudançaunclassified